2020
DOI: 10.1002/wer.1349
|View full text |Cite
|
Sign up to set email alerts
|

Oxygen transfer and plant‐wide energy assessment of primary screening in WRRFs

Abstract: Primary screening is gaining interest as a method to achieve removal performances comparable to primary clarification while reducing the footprint and increasing operational elasticity. Aeration efficiency indicators in a pilot sequential batch reactor (SBR) and a full scale water resource recovery facility (WRRF) were investigated after the implementation of rotating belt filters/screens (RBF). To compare the impact between screened (350 μm) and nonscreened primary influent, two identical treatment lines were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 35 publications
(59 reference statements)
0
1
0
Order By: Relevance
“…Thus, such treatments can be optimized to selectively remove solids by engineering the sieving process, targeting different chemical oxygen demand (COD) fractions to improve downstream water quality and maximize the potential for energy and resource recovery (Sarathy et al, 2015; Taboada‐Santos et al, 2019). A pilot‐ and full‐scale study showed a significant reduction in energy consumption with primary sieving with an RBF compared with a conventional PC due to improved oxygen transfer efficiency (Pasini et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, such treatments can be optimized to selectively remove solids by engineering the sieving process, targeting different chemical oxygen demand (COD) fractions to improve downstream water quality and maximize the potential for energy and resource recovery (Sarathy et al, 2015; Taboada‐Santos et al, 2019). A pilot‐ and full‐scale study showed a significant reduction in energy consumption with primary sieving with an RBF compared with a conventional PC due to improved oxygen transfer efficiency (Pasini et al, 2021).…”
Section: Introductionmentioning
confidence: 99%